Does 3rd dredge-up reduce AGB mass-loss?. Issue Volume 14:Issue S343(2019) (August 2018) - Uttenthaler, Stefan; McDonald, Iain; Bernhard, Klaus; Cristallo, Sergio; Gobrecht, David
Abstract: We follow up on a previous finding that Miras containing the third dredge-up (3DUP) indicator technetium (Tc) in their atmosphere form a different sequence of K – [22] colour as a function of pulsation period than Miras without Tc. A near-to-mid-infrared colour such as K – [22] is a good probe for the dust mass-loss rate (MLR) of these AGB stars. Contrary to what one might naïvely expect, Tc-poor Miras show redder K – [22] colours (i.e. higher dust MLRs) than Tc-rich Miras at a given period. In the follow-up work, the previous sample is extended and the analysis is expanded towards other colours and ISO dust spectra to check if the previous finding is due to a specific dust feature in the 22 μ m band. We also investigate if the same two sequences can be revealed in the gas MLR. Different hypotheses to explain the observation of two sequences in the P vs. K – [22] diagram are discussed and tested, but so far none of them convincingly explains the observations.